Depresja dzieci i młodzieży jako skutek problemów osobniczego i społecznego rozwoju (dokument dostępny po zalogowaniu tylko dla osób z dysfunkcją wzroku) - Ćwikliński, Andrzej (Warszawa: Komitet Nauk Pedagogicznych PAN)
The article deals with the issue of depression in children and adolescents as a shortcut to problems of individual and social development. It presents the concept of depression and its typologies, showing depression as a disease increasingly common among children and adolescents.
Keywords: depresja psychiczna; dzieci i młodzież; rozwój społeczny; problemy indywidualne; depression of children and adolescents; causes of depression; individual problems; social development